In Our Backyard How 3 L.A. Neighborhoods Affect Kids' Lives - Pebley, Anne R. (RAND Corporation, 2002)
Focusing on the subtle interaction between children's well-being and the neighborhoods in which they grow up, the authors consider the age of the community's residents, their incomes, and residential turnover in the neighborhood to draw inferences from the Focused Study of Children and Neighborhoods (FSCN), a survey of three neighborhoods in Los Angeles conducted in 1998. Drawing on the Focused Study of Children and Neighborhoods, a survey of three neighborhoods in Los Angeles conducted in 1998, the authors address the subtle interaction between children's well being and the neighborhoods in which they grow up. The authors consider the age of the community's residents, their incomes, and residential turnover in the neighborhood. The next step in this process will be a large-scale survey of children living in 65 neighborhoods throughout Los Angeles County, called the Los Angeles Family and Neighborhood Survey (L.A.FANS).